Female Community Health Volunteers in Community-Based Health Programs of Nepal: Future Perspective - Khatri, Resham Bahadur; Mishra, Shiva Raj; Khanal, Vishnu (Frontiers in Public Health, 2017)
Nepal’s Female Community Health Volunteers program started in 1988 to promote and distribute the family planning commodities. Over past three decades, their roles have gradually expanded to providing maternal and child health services at a large scale. Female Community Health Volunteers are an integral part of many community-based health programs, and their roles are instrumental in linking families/communities to peripheral health institutions. However, the fragmented nature of health programs poses a challenge for the Female Community Health Volunteers to coordinate activities and deliver the services. This perspective aims to review their contribution, challenges and recommend an integrated package to implement the programs effectively.